Heat treatment induced phase transformations in zirconia and yttriastabilized zirconia monolithic aerogels - Torres Rodríguez, Jorge Alberto; Kalmár, József; Menelaou, Melita; Čelko, Ladislav; Dvořák, Karel; Cihlář, Jaroslav; Cihlář, Jaroslav; Kaiser, Jozef; Győri, Enikő; Veres, Péter; Fábián, István; Lázár, István (Elsevier, 2019)
Monolithic, structurally stable zirconia (ZrO2) aerogels can be used in high temperature applications and as medical implants. The macroscopic properties of these solids can be fine-tuned by the appropriate thermal treatment of the amorphous aerogels. Herein, we investigate the thermally induced phase transitions of ZrO2 and yttria-stabilized zirconia (YSZ) monolithic aerogels. All aerogels were produced by an acid-catalyzed sol-gel technique and subsequent supercritical drying (SCD). A complete reaction mechanism is proposed for the formation of the wet gel network. Also, the phase transformations taking place during calcination were followed as function of temperature by in-situ X-ray diffraction measurements. Composition and size of the forming crystallites were calculated from the XRD data. Phase transition is controlled by the temperature-dependent growth of crystallite size during calcination up to 1200 °C. Both tetragonal and monoclinic zirconia form in pure ZrO2 aerogels, and a single tetragonal phase forms in YSZ aerogels.

Monolithic, structurally stable zirconia (ZrO2) aerogels can be used in high temperature applications and as medical implants. The macroscopic properties of these solids can be fine-tuned by the appropriate thermal treatment of the amorphous aerogels. Herein, we investigate the thermally induced phase transitions of ZrO2 and yttria-stabilized zirconia (YSZ) monolithic aerogels. All aerogels were produced by an acid-catalyzed sol-gel technique and subsequent supercritical drying (SCD). A complete reaction mechanism is proposed for the formation of the wet gel network. Also, the phase transformations taking place during calcination were followed as function of temperature by in-situ X-ray diffraction measurements. Composition and size of the forming crystallites were calculated from the XRD data. Phase transition is controlled by the temperature-dependent growth of crystallite size during calcination up to 1200 °C. Both tetragonal and monoclinic zirconia form in pure ZrO2 aerogels, and a single tetragonal phase forms in YSZ aerogels.
Heat treatment induced phase transformations in zirconia and yttriastabilized zirconia monolithic aerogels
Keywords: Aerogel; Zirconia; Yttria-stabilized zirconia; Heat treatment; Phase transformation; Aerogel; Zirconia; Yttria-stabilized zirconia; Heat treatment; Phase transformation